2017
DOI: 10.1371/journal.pone.0185093
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the reward value of faces and bodies from social perception

Abstract: Social judgments of faces are thought to be underpinned by two perceptual components: valence and dominance. Recent work using a standard key-press task to assess reward value found that these valence and dominance components were both positively related to the reward value of faces. Although bodies play an important role in human social interaction, the perceptual dimensions that underpin social judgments of bodies and their relationship to the reward value of bodies are not yet known. The current study inves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 17 publications
4
48
0
Order By: Relevance
“…Although we noted that some other studies have also found three dimensions underlying impressions of faces (Olivola, Eubanks, et al, 2014;Sutherland, Liu, et al, 2017;Wolffhechel et al, 2014), major models of facial first impressions are often couched in terms of two underlying dimensions Walker & Vetter, 2009), as is a leading model of intergroup perception (Fiske et al, 2007). Moreover, whilst a comparable two-dimensional structure has been found for voice perception (McAleer, Todorov, & Belin, 2014), it was not so clearly evident in a study of impressions based on bodies, where one general valence dimension appeared to be sufficient (Morrison, Wang, Hahn, Jones, & DeBruine, 2017). In parallel, there is currently a debate in the social psychological literature as to whether two or three dimensions (morality, competence, and/or sociability) best describe interpersonal and intergroup relationships outwith face perception (Brambilla, Rusconi, Sacchi, & Cherubini, 2011;Fiske et al, 2007).…”
Section: Wider Implicationsmentioning
confidence: 92%
“…Although we noted that some other studies have also found three dimensions underlying impressions of faces (Olivola, Eubanks, et al, 2014;Sutherland, Liu, et al, 2017;Wolffhechel et al, 2014), major models of facial first impressions are often couched in terms of two underlying dimensions Walker & Vetter, 2009), as is a leading model of intergroup perception (Fiske et al, 2007). Moreover, whilst a comparable two-dimensional structure has been found for voice perception (McAleer, Todorov, & Belin, 2014), it was not so clearly evident in a study of impressions based on bodies, where one general valence dimension appeared to be sufficient (Morrison, Wang, Hahn, Jones, & DeBruine, 2017). In parallel, there is currently a debate in the social psychological literature as to whether two or three dimensions (morality, competence, and/or sociability) best describe interpersonal and intergroup relationships outwith face perception (Brambilla, Rusconi, Sacchi, & Cherubini, 2011;Fiske et al, 2007).…”
Section: Wider Implicationsmentioning
confidence: 92%
“…However, the dimensional modelling approach has been increasingly influential in explaining other aspects of social perception. Our current approach can be applied in future to test dimensional models of social perception across fields, including for voices (McAleer, Todorov, & Belin, 2014), bodies (Morrison, Wang, Hahn, Jones, & DeBruine, 2017) and relationship partner preferences (South Palomares et al, 2018). Our approach can also be extended to test other populations across age and culture.…”
Section: Future Directionsmentioning
confidence: 99%
“…Our current approach can be applied in future to test dimensional models of social perception across fields, including for voices (McAleer, Todorov, & Belin, 2014), bodies (Morrison, Wang, Hahn, Jones, & DeBruine, 2017) and relationship partner preferences (South Palomares et al, 2018). Our approach can also be extended to test other populations across age and culture.…”
Section: Future Directionsmentioning
confidence: 99%